Study of ecological and developmental divergence of Icelandic Arctic charr (Salvelinus alpinus) at different scales - Nahal Eskafi 1978- (2022)
Arctic charr (Salvelinus alpinus) has been called the most variable vertebrate on the planet. It is highly diverse in morphology (size, color, and form), behavior, life history, and ecology. Lake Thingvallavatn, the biggest natural waterbody in Iceland, harbours four sympatric morphs. Moreover, allopatric charr populations in the country differ substantially. This thesis focuses on ecological variation within species on different scales, size, geology and time. Specific genetic variations in the genome and the expression of candidate genes during development in sympatric morphs of Thingvallavatn were studied in manuscript one, and variation in life-history traits in diverse populations, either in sympatry or in different watersheds, that differ in evolutionary age was analyzed, in the second manuscript. The work involved bioinformatic analyses, qPCR, otolith imaging and age-determination and various statistical analyses. The results revealed differentially expressed (Sting, Hvcn1, and Med4) genes close to (<250 kb) genetic variants with high differentiation between morphs. Moreover, 32.7% of differentially expressed genes (found in previous projects) reside in regions with strong genetic separation. The patterns of morph differences for expression and genetic separation were generally congruent. Furthermore, the data suggest the evolution of life-history traits, including age at sexual maturity and size after colonization of freshwater by sea-run (Anadromous) charr ~12.000 or fewer years ago. In comparison to anadromous charr, the resident charr mature generally when they are older and smaller, the exception being the small benthic charr. Arctic charr are a good system to study evolution of morphology and life-history traits. Bleikja (Salvelinus alpinus) hefur verið kölluð fjölbreytilegasta hryggdýr jarðar. Hún er mjög breytileg í formi (stærð, lit og lögun), hegðun, lífssöguþáttum og vistfræði. Í Þingvallavatni, stærsta náttúrulega vatni landsins finnast t.d. fjögur samsvæða bleikjuafbrigði. Einnig finnast ...